Implementation Of Warm Red Ginger Compress To Reduce Lower Back Pain In Pregnant Women In The Thirty-Trimester Through The Colcaba Comfort Theory Application In The Working Area Of The Ujan Mas Community Health Center, Kepahiang Regency - Ena Ena; Sulastri Sulastri (Utami Publisher, 2026)
Pregnancy is a remarkable process that occurs in a woman's uterus, lasting 280 days, or 40 weeks, from the first day of her last menstrual period. The purpose of this study is to understand and implement warm red ginger compresses to reduce lower back pain in third-term pregnant women through the application of the Colcaba Comfort Theory in the Ujan Mas Community Health Center, Kepahiang RegencyThe research method used in this study is a case study, which explores the application of warm red ginger compresses to reduce lower back pain in third-term pregnant women through the application of the Colcaba Comfort Theory in the Ujan Mas Community Health Center, Kepahiang Regency. The results of the study on clients 1 and 2 showed that acute pain in Cases 1 and 2 could be resolved, thus concluding that the Application of Warm Red Ginger Compresses Reduces Lower Back Pain in Pregnant Women in the 3rd trimester. It is hoped that Community Health Centers will support the use of safe non-pharmacological therapies, such as warm red ginger compresses, in managing pain in pregnant women by providing adequate facilities and equipment.